Industry-academia collaboration in MIAD strengthens countrys advanced TVET field - Nor Salwana, Mohammad Idris (UMPSA, 2024)
KUALA LUMPUR, 11 June 2024 – The MTUN Industry-Academia Discourse on Advanced TVET (MIAD) 2024 programme organised by the Malaysian Technical Universities Network (MTUN) successfully brought together an expert group of world leaders, policymakers, researchers and industry experts to explore the future of advanced TVET globally.